Infecções hospitalares em pediatria : a importância dos vírus respiratórios como agentes destas enfermidades - Florêncio, Caroline Mary Gurgel Dias (2014)
Nosocomial infections (NI) are a serious public health problem. Knowledge about the etiology of NI is important for the development of control measures, prevention and treatment. Viruses are important etiologic agent of NI has been studied in populations considered at risk as premature, heart disease, lung disease, and immunosuppressed. Respiratory hospital infection (RHI) generate discomfort to patients, postponing medical interventions, postoperative complications, use more drugs and, in some cases, intensive care, may progress to cure or to death. Viruses are responsible for outbreaks of RHI in wards and intensive care units, with the virus as detected respiratory syncytial virus. In our country there are few data on the impact of RHI caused by respiratory viruses in children. Aims of the study were: identify and describe RHI cases in children and submit nasopharyngeal aspirates collected from January to December 2013 to search for molecular diagnosis 13 respiratory viruses [respiratory syncytial virus (RSV), adenovirus, influenza A and B, parainfluenza virus -1 ,-2 , -3 and -4 , metapneumovirus and human coronavirus OC43 , NL63 , 229E and HKU - 1]. During the study period, 120 samples were included in the study and 65 % were positive for at least one virus. A total of 114 viruses were detected (33 RSV, 32 adenovirus, 14 Parainfluenza -3, 14 influenza A , 12 Parainfluenza -4 , 5 parainfluenza -1 , 3 metapneumovirus and 1 coronavirus OC43). Co-detections occurred in 26 cases: 16 with two viruses and 10 with three viruses. No clinical differences between positive and negative RHI for viruses investigated were observed. Respiratory virus were detected in four of five deaths (5/120 4.16%) associated RHI. The knowledge about the occurrence of viral RHI in association with the period of viruses circulation in the community, as described in the study, allows to develop specific actions steps to prevent and control hospital outbreaks caused by viruses.